(untitled) (Scientia Agropecuaria, 2023)
In the present review, with the help of the descriptive method, some main highlights regarding the possibilities for the valorization of passion fruit waste are systematically presented. To the best of the author’s knowledge, there is still no published review in the English-language scientific literature that examines opportunities, prospects and challenges for the valorization of passion fruit waste. For the preparation of the current review, scientific publications referenced in some of the most authoritative world-renowned scientific databases were used (Scopus, Web of Science, PubMed, Google Scholar); book chapters were not included. This review does not aim to cover, compile and describe all the scientific production available under the keywords “passion fruit waste”, but aims to highlight only some major research trends regarding the possibilities of valorization of passion fruit waste. Scientific articles that remained for technical or other reasons beyond the scope of the current review paper could be included in a subsequent updated review.